STRATEGIES FOR TEACHING LISTENING TO STUDENTS WITH DIVERSE LEARNING NEEDS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores effective strategies for teaching listening skills to learners with diverse learning styles. It begins by outlining the concept of learning styles—visual, auditory, kinesthetic, and reading/writing—highlighting how each style influences how students absorb and process information. The article then presents practical strategies for engaging learners based on their preferred learning styles. For visual learners, it recommends using videos, images, and mind maps; for auditory learners, it suggests interactive discussions and focused listening exercises;